2022
DOI: 10.7717/peerj.13217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracts from eggs of Helix aspersa maxima and Helix aspersa aspersa snails on Caco-2 colon cancer cells

Abstract: Background Colorectal cancer is the third most commonly diagnosed cancer. Natural compounds, administered together with conventional chemotherapeutic agent(s) and/or radiotherapy, may be a novel element in the combination therapy of this cancer. Considering the anticancer properties of compounds derived from different tissues of various snail species confirmed earlier, the purpose of the present research was to evaluate the effect of extracts from eggs of Helix aspera maxima and Helix aspersa aspersa snails, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 151 publications
0
12
0
Order By: Relevance
“…Another study reported that E. desertorum mucin was found to have anti-cancer activity against two types of tumor cells; CACO-2 and HepG2 cells (Atta et al, 2021). A recent study on a similar species reported that the anti-tumor effect of Helix aspersa eggs on colon cancer cells (Caco-2) (Matusiewicz et al, 2022). Treatment EACbearing mice with combination of Cis/EDEP showed significant decrease in the total tumor volume and the total cells count as same as EAC-bearing mice that had treated with Cis only which means that EDEP did not affect the efficacy of Cis .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that E. desertorum mucin was found to have anti-cancer activity against two types of tumor cells; CACO-2 and HepG2 cells (Atta et al, 2021). A recent study on a similar species reported that the anti-tumor effect of Helix aspersa eggs on colon cancer cells (Caco-2) (Matusiewicz et al, 2022). Treatment EACbearing mice with combination of Cis/EDEP showed significant decrease in the total tumor volume and the total cells count as same as EAC-bearing mice that had treated with Cis only which means that EDEP did not affect the efficacy of Cis .…”
Section: Discussionmentioning
confidence: 99%
“…Before each analysis, water extracts from dry yeast biomass, in the optimal concentration, were prepared, as in Matusiewicz et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…Ferric-reducing antioxidant power was determined in the extracts according to the modified Oyaizu method ( Matusiewicz et al, 2019 , 2022 ), n = 6.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations